Zollinger-Ellison syndrome in a child: medical treatment with cimetidine. Issue 3 (March 1980) - Drake, D P; Maciver, A G; Atwell, J D
Abstract : A 12-year-old boy presented with intestinal obstruction associated with duodenal and oesophageal ulceration. At laparotomy he was found to have an islet cell tumour in the right lobe of the liver. Gastroenterostomy was performed. Raised levels of serum gastrin were detected. Treatment with cimetidine has produced satisfactory control of his symptoms for 16 months, and is an acceptable alternative to total gastrectomy in childhood.